Bacterial Vaginosis: Risk of Adverse Pregnancy Outcome - Arif Faruqui (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
The reproductive health of a woman is vital not only for her general health, but also for that of her partner and child. Bacterial infections can affect pregnant women from implantation of the fertilized ovum through the time of delivery and peripartum period. They may also affect the fetus and newborn. Symptomatic pregnant women with confi rmed bacterial vaginosis should be treated. Treatment of pregnant women with asymptomatic bacterial vaginosis is controversial. Guidelines from the Centers for Disease Control and Prevention (CDC) recommend treating asymptomatic high-risk pregnant women with bacterial vaginosis. Antibiotic treatment can eradicate bacterial vaginosis in pregnancy but overall risk of preterm birth (PTB) is not signifi cantly reduced. Present antibiotic therapy (metronidazole and clindamycin), both oral and vaginal, do not reduce the risk of PTB. Probiotics have capability to increase vaginal lactobacilli, restore the vaginal microbiota to normal and hence helps to cure bacterial vaginosis. Therefore, Probiotics should be considered as part of the prevention and as an adjunct to antimicrobial treatment approach for BV.